The Application of the Accelerated Learning Cycle, Brain-based Learning Model, and Direct Instruction Model toward Mathematical Reasoning in Terms of Mathematical Communication - Kusuma, Arie Purwa; Rahmawati, Nurina Kurniasari; Ramadoni, Ramadoni (Universitas Islam Raden Intan Lampung, INDONESIA, 2020)
The students' mathematical reasoning and mathematical communication abilities are influenced by several factors such as the use of learning models used by teachers in learning. The use of appropriate learning models can increase students' mathematical communication abilities and reasoning. This study aims to determine the effect of the Accelerated Learning Cycle, Brain-based learning model and Direct Instruction learning models on students' mathematical reasoning abilities seen from their communication abilities. This is a quasi-experimental research. The data were analyzed using analysis of variance with unequal cells. This study concludes that, first, Accelerated Learning Cycle provides better mathematical reasoning abilities than the Brain-based learning model and the Direct Instruction learning model and Brain-based learning model provide better mathematical reasoning abilities than the Direct Instruction learning model. Second, students who have high mathematical communication abilities have better mathematical reasoning than students with moderate or low mathematical communication abilities, students who have medium communication abilities have better mathematical reasoning than students with low mathematical communication abilities